Giant intermuscular lipoma of neck and chest: a case report with review of literature - Kumari, K. Lakshmi; Babu, P. V. S. S. Vijaya; Kumar, S. V. (International Journal of Research in Medical Sciences, 2017)
Intermuscular lipoma is an uncommon benign tumor. In this case report we described a case of a patient with intermuscular lipoma located between sternocleidomastoid, pectoralis and scalene muscles on left side. These types of tumors are exceedingly rare in head and neck regions. Intermuscular lipomas are thought to arise from the Intermuscular septa and enlarge between muscle bundles. Clinical data, investigations, Magnetic Resonance Imaging scan confirm the diagnosis. These tumours are more common in males than females. Complete surgical excision of tumor is the treatment of choice. It is crucial for the surgeon to consider deep lipomas when dealing with soft tissue tumors.